2010
DOI: 10.1021/cg1003484
|View full text |Cite
|
Sign up to set email alerts
|

Layered Calcium Structures ofp-Phosphonic AcidO-Methyl-Calix[6]arene

Abstract: Hexamethoxy-calix[6]arene has been fully functionalized with p-phosphonic acid groups on the upper rim in 57% yield over three steps, and has been authenticated in the solid state by X-ray diffraction as either a nitrate salt or one of two calcium complexes. The latter differ by the ratio of calcium ions per calixarene, either 3:1 or 4:1. In both structures the coordination sphere of the calcium ions is made up of oxygen atoms from the phosphonic acid groups and from water of crystallization, as part of extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…p-Phosphonated calix [4]arene binds calcium ions, also with two solid state structure being structurally authenticated 40 which differ in the amount of calcium ions incorporated, one calcium 'rich', Fig. 8d, and one calcium 'poor', Fig.…”
Section: Metal Ion Complexationmentioning
confidence: 99%
“…p-Phosphonated calix [4]arene binds calcium ions, also with two solid state structure being structurally authenticated 40 which differ in the amount of calcium ions incorporated, one calcium 'rich', Fig. 8d, and one calcium 'poor', Fig.…”
Section: Metal Ion Complexationmentioning
confidence: 99%
“…In the case of 3 , the surface structure has a repeat unit of 45 Å, which is similar to the value of 50 Å found by Houmadi et al for the four-layer structure they observed in the presence of p -sulfonatocalix[6]arene. In addition, a crystalline calcium compound with p -phosphonatocalix[6]arene has a unit cell with a = 14.0340 Å, b = 16.2130 Å, and c = 19.4062 Å . The half-repeat value of 22–25 Å and the value of 16 Å from the atomic-resolution image shown in Figure B are comparable to the c and b values, respectively, of the calcium structure, especially given that a barium compound would be likely to form a larger unit cell than an analogous calcium compound.…”
Section: Resultsmentioning
confidence: 84%
“…For example, the uptake of calcium ions in the solid state involving a similar arrangement of bilayers with variable amounts of calcium ions incorporated between them is associated with different degrees of deprotonation of the phosphonic acid moeities. 10,12 p-Phosphonated calix[6]arene bearing O-methyl groups at the lower rim also binds Ca 2+ ions in the solid state, with a classical 'double partial cone' conformation for the hexameric ring system. 12 In further developing the metal ion chemistry of p-phosphonatocalix[n]arene we have explored the binding of sodium ions with the smallest ring system, n = 4.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 p-Phosphonated calix[6]arene bearing O-methyl groups at the lower rim also binds Ca 2+ ions in the solid state, with a classical 'double partial cone' conformation for the hexameric ring system. 12 In further developing the metal ion chemistry of p-phosphonatocalix[n]arene we have explored the binding of sodium ions with the smallest ring system, n = 4. A focus is on understanding how the assembled solids deal with a greater build up of charge on the calixarene associated with varying the level of deprotonation of the phosphonic acid moieties for a simple monovalent metal ion.…”
Section: Introductionmentioning
confidence: 99%